Implementasi Budaya Sekolah Islami dalam Penguatan Karater Religius Siswa di SMK Muhammadiyah 2 Andong - Ihwan Dahlan Prasetyo; Hafidz Hafidz (Kamaya: Jurnal Ilmu Agama, 2026)
The decline in social ethics and religious discipline among adolescents amidst modern disruption requires vocational education institutions to strengthen the spiritual character of students in a structured manner. This study aims to analyze the actualization of Islamic school culture in strengthening students' religious character while measuring its implications at SMK Muhammadiyah 2 Andong. This study uses a qualitative approach with a descriptive design located at SMK Muhammadiyah 2 Andong. Data were collected through direct observation techniques, in-depth interviews, and document reviews from three informants selected through purposive sampling: one main informant (Deputy Head of AIK), one teacher with a minimum of three years of teaching experience, and one student who is characterized as a religious activity administrator. Data analysis was carried out using the Miles and Huberman model which includes data reduction, data presentation, and conclusion drawing, and its validity was tested using source and technique triangulation. The main findings indicate that the actualization of Islamic culture in schools is realized concretely through programs to habituate worship, cultivate Islamic ethics, study of Al-Islam and Muhammadiyah, and religious extracurricular activities. The implementation strategy is synergistically supported by consistent habituation, exemplary teacher behavior, direct supervision based on participatory evaluation, and the creation of a religious environment. In conclusion, Islamic school culture has been proven to have a positive impact on strengthening students' spiritual dimension by increasing intrinsic awareness of worship and strengthening the social dimension through improved interaction ethics, respect for teachers, and harmony among peers.